PERAN SEKOLAH SEPAKBOLA (SSB) MONDOTEKO PUTRA REMBANG TERHADAP PERKEMBANGAN SEPAKBOLA (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study is to determine the role of the Football School ( SSB ) Mondoteko Putra Rembang towards the development of football in the district of Rembang. The method used in this research is descriptive method. Based on the results of the research, SSB Mondoteko Putra Rembang players accounted in Porseni for junior grade for as much as 75 %, Popda high school level: 60 % players, Porprop level: 44% players and there are two players have entered PSIR Rembang. Fotball School Mondoteko Putra Rembang has an important position in the development of football in the district of Rembang. It can be concluded that SSB Mondoteko Putra Rembang contributes to the development of football in the district of Rembang in the field of sport, breeding, and training such as the providing training facilities, operational funding support, at the most, participating in the tournament which brings honor and pride for Rembang. Some suggestions from the researcher are that SSB Mondoteko Putra Rembang will retain the prideful achievement of Rembang, will keep doing the football coaching in stages and improve the quality of the training in SSB. Also, there is a suggestion to Rembang Local District Government to give more attention to SSB Mondoteko Putra Rembang.